Exploring the Esoteric Dimensions of the Tijāniyyah Ṣūfī order: A critique of Ṣalāt al-fātiḥ and Jawharat al-kamāl - Kolawole, Hakeem Adeyinka; Che Amnah binti Bahari (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2024)
Abstract The study of Ṣūfī orders and their activities has attracted significant scholarly interest, underscoring the complexities of their rituals, beliefs, and historical evolution. This writeup provides a critical examination of two key (wirds) from the Tijāniyyah Ṣūfī order: Ṣalāt al-fātiḥ and Jawharat al-kamāl. These concepts are crucial to the Tijāniyyah tradition, offering insight into its theological foundations and spiritual practices. However, the practices of Ṣalāt al-fātiḥ and Jawharat al-kamāl have been subjects of both veneration and controversy. While they are central to the spiritual life of Tijāniyyah adherents, they have also faced criticism from various quarters, including concerns about their orthodoxy, exclusivity, and the claims of spiritual efficacy associated with them. This writing critiques these two formulas and compares them with the dictates of the Qur’ān and Sunnah, aiming to discuss the opposing views of both the proponents and opponents. The critique also addresses the controversies surrounding the claims of exclusivity, divine origin, and the elevated status of these prayers compared to traditional Islamic supplications. It adopts a qualitative method, utilising library materials such as books, journals, articles and other relevant sources. It also employs a structured interview to analyse the Tijāniyyah practices. The writing finds that Ṣalāt al-fātiḥ and Jawharat al-kamāl are deeply embedded in the Tijāniyyah tradition and are perceived as essential for spiritual progress by adherents. However, both within and outside the order, critiques highlight concerns about the practices’ alignment with Islamic orthodoxy and exclusivity. The finding suggests that while these practices are meaningful to their practitioners, they also reflect the broader tensions within Islamic thought regarding tradition, innovation, and the diversity of spiritual expression.